2013
DOI: 10.1016/j.chembiol.2013.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Interaction with BCL-2 Family Proteins Underlies the Proapoptotic Activity of PUMA BH3

Abstract: SUMMARY PUMA is a pro-apoptotic BCL-2 family member that drives the apoptotic response to a diversity of p53-dependent and independent cellular insults. Deciphering the spectrum of PUMA interactions that confer its context-dependent pro-apoptotic properties remains a high priority goal. Here, we report the synthesis of PUMA SAHBs, structurally-stabilized PUMA BH3 helices that, in addition to broadly targeting anti-apoptotic proteins, directly bind to BAX. NMR, photocrosslinking, and biochemical analyses reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
69
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 70 publications
3
69
0
Order By: Relevance
“…Hence, our observation that Puma priming of CAF for cell death was Bakdependent was unexpected, especially because Puma can activate either Bak or Bax (40,41). Additionally, in our prior studies using CAF, Bax was found to participate in the priming phenomenon (3).…”
Section: Discussionmentioning
confidence: 87%
“…Hence, our observation that Puma priming of CAF for cell death was Bakdependent was unexpected, especially because Puma can activate either Bak or Bax (40,41). Additionally, in our prior studies using CAF, Bax was found to participate in the priming phenomenon (3).…”
Section: Discussionmentioning
confidence: 87%
“…Because BID is not constitutively active (cleaved) in these cells (Meng et al 2007(Meng et al , 2010, our studies examined the potential role of BIM and PUMA. If these activator proteins were responsible for constitutive BAK activation, one would expect (1) that BIM and PUMA knockdown would diminish constitutive BAK activation and (2) that BAX, which is preferentially activated by these BH3-only proteins (Edwards et al 2013;Sarosiek et al 2013), would also be activated. Contrary to these predictions, down-regulating BIM and PUMA had little effect on basal BAK oligomerization ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…According to one model, their activation is triggered when cellular stresses lead to increased expression or activity of BH3-only members of the BCL2 family, such as BIM, PUMA, or BID (Chipuk and Green 2008;Strasser et al 2011;Czabotar et al 2014). Sharing homology in a single 15-amino-acid α-helical domain Westphal et al 2014), these proapoptotic proteins bind transiently to the hydrophobic groove of BAX or BAK (Dai et al , 2014Czabotar et al 2013;Edwards et al 2013;Brouwer et al 2014) or a secondary site on BAX (Gavathiotis et al 2008;Edwards et al 2013) to facilitate BAX/BAK oligomerization (Antonsson et al 2001;Cheng et al 2003) and MOM permeabilization (MOMP). Evidence in support of this direct activation model includes direct binding of BH3-only proteins (Kim et al 2009;Dai et al 2011Dai et al , 2014 or BH3 peptides (Walensky et al 2006;Gavathiotis et al 2008;Czabotar et al 2013;Brouwer et al 2014) to BAX or BAK in vitro as well as the ability of this binding to trigger BAX/ BAK oligomerization and membrane permeabilization in cell-free systems (Kuwana et al 2002;Letai et al 2002;Dewson et al 2008Dewson et al , 2009Lovell et al 2008;Oh et al 2010;Dai et al 2011;Du et al 2011).…”
mentioning
confidence: 99%
“…A mechanistic study has shown that the lead compound A-1210477 and related analogs can disrupt the interactions of MCL-1 with BIM and NOXA, penetrate living cells, and act via an on-target mechanism. BaX activator putative puma-Bh3 peptide 42,43 Bak activator putative puma sahB analog 44 BaX activator and BCL-2/mCL-1 inhibitor putative…”
Section: Discovery Of Novel Bh3 Mimeticsmentioning
confidence: 99%
“…The BH3-mimetic strategy has lastly allowed the discovery of a small molecule with particular properties. 44 A stapled peptide derived from the PUMA BH3 region (called PUMA SAHB) has been found to not only bind and inhibit BCL-2 and MCL-1 but also directly bind and activate BAX. A cell permeable analog of PUMA SAHB (and exhibiting the same properties) has been shown to elicit mitochondrial apoptosis in neuroblastoma cells.…”
mentioning
confidence: 99%